2014
DOI: 10.1186/1756-0500-7-708
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the need and identifying goals for a curriculum in medical business ethics: a survey of students and residents at two medical centers in Missouri

Abstract: BackgroundIn recent years, issues in medical business ethics (MBE), such as conflicts of interest (COI), Medicare fraud and abuse, and the structure and functioning of reimbursement systems, have received significant attention from the media and professional associations in the United States. As a result of highly publicized instances of financial interests altering physician decision-making, major professional organizations and government bodies have produced reports and guidelines to encourage self-regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Billing errors and mistakes, misclassification of a diagnosis or procedure, or improper documentation can indicate lack of program integrity education. 16,17,18 Inaccurate coding or errors in documentation can result from improper or incomplete interaction with the patient's electronic health record (EHR) if the physician merely copies and pastes text, if the EHR self-populates from previous encounters, or if the algorithm prompts the physician to offer the patient potentially unnecessary or inappropriate services. 16,17 When do these types of behaviors become fraud?…”
Section: Incentivized To Process More Patients?mentioning
confidence: 99%
See 1 more Smart Citation
“…Billing errors and mistakes, misclassification of a diagnosis or procedure, or improper documentation can indicate lack of program integrity education. 16,17,18 Inaccurate coding or errors in documentation can result from improper or incomplete interaction with the patient's electronic health record (EHR) if the physician merely copies and pastes text, if the EHR self-populates from previous encounters, or if the algorithm prompts the physician to offer the patient potentially unnecessary or inappropriate services. 16,17 When do these types of behaviors become fraud?…”
Section: Incentivized To Process More Patients?mentioning
confidence: 99%
“…17 In response, some stakeholders recommend resident physician education that would cover issues pertaining to compliance, billing, appropriate documentation, adequate supervision, and potential civil and criminal liability. 16,17,18 A variety of training models exist, and several commentators suggest integrating program integrity training as part of the physician onboarding process. 16 Front-end analytics.…”
Section: Solutions To Mitigate Fraud and Abusementioning
confidence: 99%
“…In 2013 the Bander Center surveyed medical students and residents at two academic medical centers in Missouri on "their awareness of major MBE guidance documents, knowledge of key MBE research, beliefs about the goals of an education in MBE, and the areas of MBE they were most interested in learning more about" [2]. The results revealed that "medical students and residents had little awareness of recent and major reports on MBE topics and had minimal knowledge of basic MBE facts" [2], such as what percentage of academic physicians have a financial relationship with industry. However, "both groups showed significant interest in learning more about MBE topics…such as 'the business aspects of medicine' and 'health care delivery systems'" [2].…”
Section: The Challengementioning
confidence: 99%
“…The results revealed that "medical students and residents had little awareness of recent and major reports on MBE topics and had minimal knowledge of basic MBE facts" [2], such as what percentage of academic physicians have a financial relationship with industry. However, "both groups showed significant interest in learning more about MBE topics…such as 'the business aspects of medicine' and 'health care delivery systems'" [2].…”
Section: The Challengementioning
confidence: 99%
See 1 more Smart Citation